Hydrogen storage on graphene using Benkeser reaction - Sarkar, A.Kr. (John Wiley and Sons Ltd, 2014)
Recently, graphene has received great attention as potential hydrogen storage media. Here, we report a new route to store/chemisorb high content of hydrogen on graphene by employing Benkeser reaction. Graphene nanosheets are produced via a soft chemistry synthetic route involving oxidation of graphite using Improved method, ultrasonic exfoliation, and chemical reduction by using hydrazine with overnight heat treatment. Graphene is hydrogenated by using lithium in ethylenediamine under Benkeser reaction at atmospheric pressure and 30Â°C. Benkeser reaction overcomes the liquid ammonia handling and produced multiple layer of graphene attached to the hydrogen atoms. High-resolution transmission electron microscopy and selected area electron diffraction analysis confirm the ordered graphite crystal structure of graphene and reveal the rough, corrugated hydrogenated graphene layers attached by hydrogen atoms. Fourier transformation infrared spectroscopy analysis confirms that hydrogen adsorption occurs at all the ortho, meta, and para positions of aromatic graphene. The degree of hydrogenation of graphene estimated by thermogravimetric analysis reveals 14.67 (weight ) hydrogen storage, which is considerably higher than the earlier reported values of percentage storage achieved using various physisorption and chemisorption techniques. Copyright Â© 2014 John Wiley & Sons, Ltd.